Applications of Receptor- and Ligand-based Models in Inverse Docking Experiments: Recognition of Dihydrofolate Reductase Using 7,8-Dialkyl- 1,3-Diaminopyrrolo[3,2-f]Quinazolines - Prasanth Kumar, Sivakumar; T. Jasrai, Yogesh; A. Pandya, Himanshu (Current Computer - Aided Drug Design, 2016)
Inverse (or reverse) docking approach which involves docking of a ligand against a set of protein structures to predict possible protein target(s), possess limitations, including inefficient empirical scoring schemes and similarities in protein active site shape and physico-chemical properties. To overcome this limitation, we combined receptor- and ligand-based methods to predict probable protein targets. We showed that the experimental protein target along with possible offtargets can be effectively retrieved if the docking energy of the reference molecule and probe molecules based scaled energy profiles were combined and clustered together. The present method was validated using 7,8-dialkyl-1,3-diaminopyrrolo[3,2-f]quinazolines that inhibit Candida albicans dihydrofolate reductase (DHFR) in vitro.
Keywords: molecular modeling